Investigating resilience in patients with IBD: preliminary insights for understanding disease-specific resilience skills - Mendiolaza, Michelle; Ogundipe, Tonia; Arroyave-Villada, Juan; Adeonigbagbe, Olusola; Gorbenko, Ksenia; Keefer, Laurie (Frontiers in Psychology, 2024)
Introduction: Inflammatory bowel diseases (IBDs) significantly impact patients' quality of life. While research highlights the potential role of psychological resilience to enhance overall health and well-being in patients with chronic conditions, its specific role in the context of IBD remains underexplored. This study aimed to identify key components of resilience, while serving as a precursor to the development of a disease-specific Resilience Scale for IBD (RISE-IBD). Methods: In semi-structured focus groups and individual interviews, fifteen patients with IBD discussed their perspectives on the construct of resilience, particularly in terms of the diverse strategies they employed to overcome IBD-related challenges. Patients also deliberated on the relevance of themes identified in two widely used and validated resilience measures. Four analysts coded the transcripts using MAXQDA. Selected items for the drafted measure were refined based on constructive feedback from an additional focus group with study participants and six multidisciplinary IBD professionals, thus establishing face and content validity. Results: The qualitative analysis revealed critical themes of resilience for IBD including: 1) seeking physical and emotional support from others, 2) developing personal coping mechanisms to manage stress, and 3) employing strategic disease-management techniques. These themes led to the identification of seventeen items, which were categorized into three domains: interpersonal fortitude, individual character strengths, and logistical strategies. Discussion: This study highlights the critical role of resilience, a core concept in positive psychology, in the effective self-management of IBD. The findings underscore the importance of building upon resilience strategies to help patients bolster the psychological potencies needed to manage their condition more effectively. Future research will focus on the psychometric validation of items identified for the scale. By incorporating resilience-building strategies into IBD care, we can support patients in developing a more positive outlook and improved life satisfaction.